Factors Associated With Cervical Cancer Screening Attendance in Hungary Based on the European Health Interview Survey - Jenifer Pataki; Jenifer Pataki; Gergő József Szőllősi; Attila Sárváry; Viktor Dombrádi (Frontiers Media S.A., 2024)
ObjectivesThis study assessed the change in cervical cancer screening attendance across 10 years and identified the associated factors.MethodsData from the European Health Interview Surveys in Hungary (2009, 2014, 2019) were analyzed with multivariate and multiple logistic regressions.ResultsThe analysis involved 4,850 participants, revealing a significant (p < 0.001) increase in screening attendance from 69% to 77% over 10 years. Factors significantly associated with higher attendance rates included a higher education level (tertiary level AOR = 2.51 [2.03-3.09]), being in a relationship (AOR = 1.59 [1.39-1.83]), the belief that one can do much for one's health (OR = 1.26 [1.05-1.52]), and the absence of chronic health problems (AOR = 1.56 [1.33-1.84]). Lower screening odds were significantly correlated with worse self-perceived health status (AOR = 0.65 [0.52-0.81]) and less frequent doctor (AOR = 0.64 [0.54-0.76]) and specialist visits (AOR = 0.46 [0.39-0.53]).ConclusionEnhancing cervical cancer screening rates requires tailored public health strategies, particularly targeting individuals with lower education and poor health perceptions. Public health initiatives and enhanced collaboration among healthcare professionals are required to further increase participation rates, particularly among the identified groups.